Relationship Marketing in Sports: A Functional Approach - Bee,Colleen; Kahle,Lynn (Sport Marketing Quarterly, 2006)
This paper examines how and why consumers develop, enter into, and maintain relationships in a sports marketing context. This paper presents a framework for understanding how and why consumers engage in relationship marketing. Based on Kelman's functional approach to attitude change, this framework presents three qualitatively different levels for understanding relationship formation and maintenance: (a) compliance is superficial, temporary, and often the result of external influence; (b) identification is related to self-esteem and image enhancement of sport consumers; and (c) internalization is the result of values similarity. Internalization is more likely to result in a long-term relationship.
Keywords: Marketing